World War II [compact disc] - Montagne, Renee; Simon, Scott; Cronkite, Walter (American chronicles (National Public Radio (U.S.)), 2011)
Released in time for the 70th anniversary of the bombing of Pearl Harbor, 26 stories from NPR reflect on the deadliest war in human history.